Meatal ulcer: very rare complication of Foley catheterization - Yagnik, Vipul D. (International Surgery Journal, 2017)
A 65 year old gentleman was admitted with the diagnosis of exophytic tumor arising from the stomach wall. His vitals were normal. Patient was poorly built and poorly nourished with BMI of blood chemistry, ECG, and ECHO was normal. His past medical and surgical history was not significant. Urethral catheterization was performed pre-operative with strict aseptic technique. Patient underwent   laparotomy with subtotal gastrectomy and gastrojejunostomy. Catheter care was done regularly by trained staff. Catheter was removed on third post operative day. After removal of catheter, Patient had a difficulty in passing   urine. On examination, single meatal ulcer was noted (Figure 1). Post –operative course was unremarkable. Patient is in follow up since last six month without any problem.